Knowledge, attitudes and practices of patients with chronic illnesses during the COVID-19 pandemic: A cross-sectional survey from Pakistan. (September 2022) - Mahmood, Muhammad Muzaffar; Rehman, Junaid; Arif, Bushra; Rehman, Zahra; Aasim, Muhammad; Saeed, Muhammad Tahir
Objectives: We studied the impact of the Covid-19 pandemic on the physical and mental health of patients with chronic illnesses and their behavioural responses. Methods: We conducted a cross-sectional knowledge, attitudes and practices (KAP) survey among outpatients with chronic illnesses in Lahore, Pakistan. Results: Four hundred and one participants were surveyed (84% above 50 years of age). One or two chronic illnesses were present in 130 (32%), three or four in 211 (53%) and more than four in 60 (15%). The majority correctly identified the sources of Covid-19 infection and higher risk patients. Of the respondents, 127 (32%) described feeling more vulnerable. Respondents reported a lack of trust in the community response (199; 49.6%) and hospital measures (167; 41.6%) to slow the spread of Covid-19 and 369 (92%) practiced some degree of social distancing. Respondents described negative impacts of lockdown measures on their physical and mental health (235; 58.6% and 262; 65.3%, respectively). Many reported difficulty in getting medical help during the pandemic (302; 75.2%). Half of the respondents (200; 49.8%) felt that delays in receiving care had adversely affected their health. Conclusions: Respondents with chronic illnesses frequently reported negative behavioural and health impacts during the Covid-19 pandemic.